Competence of Productive Teachers in Utilizing Learning Media Based on Information Communication Technology - Fachri, Fandi Faisyal; Muchlas, Muchlas; Santosa, Budi (Universitas Ahmad Dahlan, 2024)
The ability of teachers to create ICT-based learning media is low, despite ICT's potential to address shortages in practical equipment and facilities. This research aims to analyze vocational high school teachers' competency in utilizing ICT-based learning media and identify obstacles they face. Using a descriptive qualitative method, the study involves productive teachers, school principals, and heads of administration. It focuses on teachers with expertise in broadcasting, film, animation, and machining techniques. The research steps include problem identification, limitation, focus determination, data collection, analysis, and reporting. Findings reveal that the average competency of productive teachers in three vocational schools is good: 35.29% are at a basic level, 47.06% at intermediate, and 17.65% at advanced. Teachers learn to create ICT-based media through lectures (10 teachers), courses (6), workshops (14), training (10), and independently (3), with workshops being the most common. In practical learning, 100% of teachers use PowerPoint, 64.71% use animation, 23.53% use Moodle, and 5.88% each use Debian, Nginx, and PHP. Barriers include lack of facilities (17.65%), ICT mastery (17.65%), time (31.18%), and other reasons (23.53%).